A mathematical model for treatment-resistant mutations of HIV - Helen Moore; Weiqing Gu (Mathematical Biosciences and Engineering)
In this paper, we propose and analyze a mathematical model,in the form of a system of ordinary differential equations, governingmutated strains of human immunodeficiency virus (HIV) and theirinteractions with the immune system and treatments. Our modelincorporates two types of resistant mutations: strains that are notresponsive to protease inhibitors, and strains that are not responsiveto reverse transcriptase inhibitors. It also includes strains that do nothave either of these two types of resistance (wild-type virus) andstrains that have both types. We perform our analysis by changing thesystem of ordinary differential equations (ODEs) to a simplesingle-variable ODE, then identifying equilibria and determining stability.We carry out numerical calculations that illustrate the behavior of thesystem. We also examine the effects of various treatment regimens on thedevelopment of treatment-resistant mutations of HIV in this model.